Childhood Peutz-Jeghers Syndrome: Diversity of Clinical Features and Complications, and Literature Review - Mark R Oliver; R Brent Scott; Robin C Eccles; Cynthia Trevenen; Jonathon B Meddings; Steven R Martin (Canadian Journal of Gastroenterology)
This case report of a six-year-old child with Peutz-Jeghers syndrome illustrates the potential diversity of presenting gastrointestinal symptoms and signs including hematemesis, obstruction and recurrent intussusception. Endoscopy was useful in assessment, while endoscopic polypectomy and surgical resection were both necessary for management. The literature is reviewed and the possible role that this syndrome may have in the development of both gastrointestinal and nongastrointestinal tumours is highlighted.